2020
DOI: 10.1002/ajoc.201900749
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Iron(III) Salt as an Initiator for Radical Cation‐induced [4+2] Cycloaddition

Abstract: We developed a cationic iron(III) salt initiator for radical cation‐induced [4+2] cycloaddition. Fe(OTf)3 [or Fe(ClO4)3] behaves as a highly active oxidant for both electron‐deficient and electron‐rich dienophiles. The scope of substrates is much broader than with FeCl3 reported previously. With highly active Fe(OTf)3, we demonstrate a formal total synthesis of Heitziamide A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…[188] In order to reinvestigate iron (III) initiators for the [4 + 2] cycloaddition of electron-deficient dienophiles, Horibe et al in the year 2020 reported a cationic iron (III) salt initiator for radical cation-induced [4 + 2] cycloaddition of electron-rich dienophile 213 and electron-rich diene 214 for the synthesis of [4 + 2] cycloadduct 215 (Scheme 60). [189] Highly active Fe(OTf There are multiple literature reports of Povarov reactions [190] based on the tertiary anilines, but there is no literature report for [4 + 2] cycloaddition using a secondary aniline as the substrate. Exploiting secondary/tertiary anilines 217, Ding et al in 2021 outlined the synthesis of quinolone-spiroquinzolinones 219 by an iron-catalyzed cross-dehydrogenative coupling [4 + 2] annulation of 217 and quinazolinones 218 (Scheme 61).…”
Section: Iron Catalyzed [4 + 2] Cycloadditionsmentioning
confidence: 99%
“…[188] In order to reinvestigate iron (III) initiators for the [4 + 2] cycloaddition of electron-deficient dienophiles, Horibe et al in the year 2020 reported a cationic iron (III) salt initiator for radical cation-induced [4 + 2] cycloaddition of electron-rich dienophile 213 and electron-rich diene 214 for the synthesis of [4 + 2] cycloadduct 215 (Scheme 60). [189] Highly active Fe(OTf There are multiple literature reports of Povarov reactions [190] based on the tertiary anilines, but there is no literature report for [4 + 2] cycloaddition using a secondary aniline as the substrate. Exploiting secondary/tertiary anilines 217, Ding et al in 2021 outlined the synthesis of quinolone-spiroquinzolinones 219 by an iron-catalyzed cross-dehydrogenative coupling [4 + 2] annulation of 217 and quinazolinones 218 (Scheme 61).…”
Section: Iron Catalyzed [4 + 2] Cycloadditionsmentioning
confidence: 99%
“…Delightfully, in the following year, they explored the reaction with Fe(OTf ) 3 as a catalyst and tested substrates substituted with electron-withdrawing groups, again obtaining high yields, which successfully expanded the scope of substrates (Scheme 11b). 21 Thiophene with a conjugated diene structure has likewise been used in (4 + 2) cycloaddition reactions. In 2019, Chiang and Lei's group achieved the first visible-light-induced (4 + 2) cycloaddition reaction of thiophene and alkynes (Scheme 12).…”
Section: Aryl Radical Cationsmentioning
confidence: 99%
“…Delightfully, in the following year, they explored the reaction with Fe(OTf) 3 as a catalyst and tested substrates substituted with electron-withdrawing groups, again obtaining high yields, which successfully expanded the scope of substrates (Scheme 11b). 21…”
Section: Aryl Radical Cationsmentioning
confidence: 99%
“…Moreover, we designed the activated cinnamates possessing an additional formyl group, which would further lower the LUMO energy via vinylogous activation by potentially forming iminium ions I , as proposed in Scheme c. Therefore, such a double catalytic mode with a single amine, through simultaneous LUMO-activation of cinnamate derivatives and HOMO-activation of 2,4-dienals (via trienamines II) , would not only enhance the reactivity but also switch the regioselectivity of traditional cinnamate dienophiles in the DA reaction . Moreover, the resulting multifunctional cycloadducts III might further render a cascade intramolecular aldol reaction under aminocatalytic conditions, straightforwardly affording the polyhydrophenanthrene frameworks, a type of fused tricyclic system ambiguous in natural products and receiving wide interest in organic synthesis …”
mentioning
confidence: 99%